2013
DOI: 10.1155/2013/135314
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Attenuates Gentamicin-Induced Nephrotoxicity: Role of Mitochondrial Protection

Abstract: Sulforaphane (SFN), an isothiocyanate naturally occurring in Cruciferae, induces cytoprotection in several tissues. Its protective effect has been associated with its ability to induce cytoprotective enzymes through an Nrf2-dependent pathway. Gentamicin (GM) is a widely used antibiotic; nephrotoxicity is the main side effect of this compound. In this study, it was investigated if SFN is able to induce protection against GM-induced nephropathy both in renal epithelial LLC-PK1 cells in culture and in rats. SFN p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…In our experiments using mouse models of sepsisand IRI-induced AKI, we observed that the beneficial effects of resveratrol and ethyl pyruvate are attributed to their ability to scavenge ROS and prevent release of proinflammatory HMGB1 in the circulation (242). The renoprotective effects of resveratrol and sulforaphane (an isothiocyanate that is found in vegetables) are also mediated by their ability to upregulate NRF-2 signaling and protect mitochondrial function (149,153,200,279). The upregulation of NRF-2 results in downstream stimulation of various antioxidants, including glutathione, thioredoxin, SOD, and catalase.…”
Section: Naturally Occurring Antioxidantsmentioning
confidence: 94%
“…In our experiments using mouse models of sepsisand IRI-induced AKI, we observed that the beneficial effects of resveratrol and ethyl pyruvate are attributed to their ability to scavenge ROS and prevent release of proinflammatory HMGB1 in the circulation (242). The renoprotective effects of resveratrol and sulforaphane (an isothiocyanate that is found in vegetables) are also mediated by their ability to upregulate NRF-2 signaling and protect mitochondrial function (149,153,200,279). The upregulation of NRF-2 results in downstream stimulation of various antioxidants, including glutathione, thioredoxin, SOD, and catalase.…”
Section: Naturally Occurring Antioxidantsmentioning
confidence: 94%
“…Accordingly, application of antioxidants as natural defense against oxidative stress is of utmost significance owing to their capability to donate electrons and scavenger free radicals [10][11][12]. The popularity of phytochemicals has been on the rise, antioxidant features in particular, which are believed that their protective functions could be considered as an effective treatment of Cd poisoning [11,[13][14][15]. Curcumin is derived from the plant Curcuma longa L. [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…GM is one of the best known nephrotoxic drugs and its association with mitochondrial dysfunction in proximal tubules has been well studied [ 22 ]. Mitochondrial membrane potential disruption [ 23 ], oxygen consumption anomalies, adenosine triphosphate (ATP) yield decrease, MPT pore formation, mitochondrial cytochrome c release, intrinsic apoptosis, and mitochondrial antioxidant status impairment have been observed both in culture tubular cells and in rat kidneys exposed to GM [ 23 26 ]. On the other hand, some reports suggest that curcumin protective effect against GM nephrotoxicity is associated with preservation of the renal antioxidant status and with modulation of the inflammatory response mediated by NF- κ B, rather than with protection of renal mitochondrial function [ 20 , 21 , 27 ].…”
Section: Introductionmentioning
confidence: 99%